2017
DOI: 10.1515/nbec-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of photoassimilates transport in plant tissues by positron emission tomography

Abstract: The current findings show that positron emission tomography (PET), primarily developed for medical diagnostic imaging, can be applied in plant studies to analyze the transport and allocation of wide range of compounds labelled with positronemitting radioisotopes. This work is focused on PET analysis of the uptake and transport of 2-deoxy-2-fluoro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…In the comparison of the analyzed pepper plants, it was found that in the case of plant immersed in a 2-[ 18 F]FDG solution with the stem after removal of the root, the TFc value was 2-times higher than in the case of intact pepper plant immersed in a solution of 2-[ 18 F]FDG by the root system (TFc = 9.4). Also, it can be concluded that there was a significantly higher translocation of 2-[ 18 F]FDG and TFc values compared to the values found in previous work (Partelová et al 2014) in the case of tobacco plants (N. tabacum L.), as well as in the case of giant reed plants (A. donax L.) (Partelová et al 2017). In the work Partelová et al (2014), there were reached the values of TFc = 0.04 at D-glucose concentration 0.00762 mg.mL -1 and TFc = 0.21 at 0.762 mg.mL -1 , which indicated a significant accumulation of 2-[ 18 F]FDG in the root system and its minimal transfer to the aboveground parts of plants.…”
Section: Root System As a Barrier For 2-[ 18 F]fdg Transportcontrasting
confidence: 47%
“…In the comparison of the analyzed pepper plants, it was found that in the case of plant immersed in a 2-[ 18 F]FDG solution with the stem after removal of the root, the TFc value was 2-times higher than in the case of intact pepper plant immersed in a solution of 2-[ 18 F]FDG by the root system (TFc = 9.4). Also, it can be concluded that there was a significantly higher translocation of 2-[ 18 F]FDG and TFc values compared to the values found in previous work (Partelová et al 2014) in the case of tobacco plants (N. tabacum L.), as well as in the case of giant reed plants (A. donax L.) (Partelová et al 2017). In the work Partelová et al (2014), there were reached the values of TFc = 0.04 at D-glucose concentration 0.00762 mg.mL -1 and TFc = 0.21 at 0.762 mg.mL -1 , which indicated a significant accumulation of 2-[ 18 F]FDG in the root system and its minimal transfer to the aboveground parts of plants.…”
Section: Root System As a Barrier For 2-[ 18 F]fdg Transportcontrasting
confidence: 47%
“…Mass spectrometry-based imaging like the matrix-assisted laser-desorption ionization technique can detect various classes of metabolites (Boughton et al, 2016;Murray et al, 2016), but its level of resolution and specificity is compromised when the detection target is, like Suc, of low M r (issues with matrix effects). Positron emission tomography has been used to trace photoassimilate allocation, but so far it has been unable to demonstrate a sufficient level of chemical or spatial resolution when targeted to Suc (Partelová et al, 2017). Magnetic resonance imaging (MRI) is able to measure Suc in a label-free manner in vivo , but its imaging is difficult when Suc is present at a low concentration (Borisjuk et al, 2012).…”
mentioning
confidence: 99%
“…Partelová et al later used PET to image [ 18 F]FDG uptake and transport in giant reed ( Arunda donax ) seedlings dosed through intact roots, damaged roots, excised stem, and cut leaf. 85 [ 18 F]FDG uptake into plants was limited when applied through a cut leaf; however, the other dosing methods resulted in [ 18 F]FDG accumulation in the plant. Roots were primary regions of accumulation in plants with roots (damaged or intact), but some [ 18 F]FDG translocated to aboveground structures.…”
Section: Positron Imaging For Visualization Of Carbon Dynamics In Plamentioning
confidence: 99%
“…The application of positron imaging to plant studies has increased significantly since the initial water transport analyses by McKay et al 2 While dynamics of water movement with PET in plants has been widely studied, [25][26][27][28][29][30][31][32][33][34][35] other topics related to PET have increasingly been investigated, including uptake and translocation of nutrients, [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]98,99 photoassimilate fixation/allocation, 15,22,23, sugar transport, 21,[82][83][84][85][86][87] and heavy metal contaminant uptake and transport 25,[88][89][90][91][92][93]…”
Section: Physics Of Positron Detection In Plant and Soil Systemsmentioning
confidence: 99%